A Comparative Study of Indigent Defense in the State of Kansas - Powell, Ethan J. (My University, 2019)
In the decades since the Supreme Court handed down its landmark decision in Gideon v. Wainwright in 1963, significant nationwide debate has surrounded the methods and means by which the right to legal representation for indigent defendants should be upheld. Issues of efficiency, due process, adequate defense, and the breadth of charges which the state is constitutionally bound to protect have all colored how this subject is legislated and held in the public imagination. This research project is designed to describe, analyze, and evaluate the indigent defense process across the state of Kansas. To this end, quantitative and qualitative data on three separate jurisdictions in areas of varying population density will be compiled and assessed. These include the State Indigent Defense Offices in Shawnee County and Junction City, as well as the assigned counsel system present in Marshall County. Factors such as attorney caseloads, the funding of these institutions, and the likelihood that defendants in a given jurisdiction will qualify for indigence will be considered to better understand the experience that disadvantaged defendants across the state have with the criminal justice system. While a relatively small sample of jurisdictions will not provide an irrefutably conclusive picture of the current state of indigent defense in Kansas, this case study will contribute significant regional information to the ongoing national conversation on the subject.